The Application of a Generational Approach to the Marketing Management of Gerês-Xurés Cross-Border Park (Portugal and Spain) - Nogueira, Sónia (2022)
The purpose of this study is to understand the importance of the application of generational marketing tools to generational groups visiting Gerês-Xu- rés cross-border Park (Portugal and Spain), considering their natural values, the specific consumer behavior giving insights about the most effective marketing tools for natural parks tourism destination promotion. The study adds value to the existing literature on the theory of generational marketing because it assesses its applicability to the concrete case of cross-border parks (an area that stills little explored from the conceptual point of view and the application of specific marketing techniques adapted to this type of concrete reality). As a result of the study, it was found that considering marketing activities of the entities involved in the cross-border park promotion as a nature destination are used a combination of tools of both online and offline marketing, for generations baby boomers, generation X, Y, Z and Alpha with an emphasis on experience marketing that contributes to a growth in visitors to the Gerês-Xurés cross-border Park.